2005
DOI: 10.1111/j.0022-202x.2005.23915.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Salivary Gland Extracts Induce EBV-Infected NK Cell Oncogenesis Via CD4+ T Cells in Patients with Hypersensitivity to Mosquito Bites

Abstract: Severe hypersensitivity to mosquito bites (HMB) is characterized by intense local skin reactions and systemic symptoms such as high fever, lymphadenopathy, and hepatosplenomegaly. Patients with HMB often have natural killer (NK) cell lymphocytosis associated with Epstein-Barr virus (EBV) infection. Here we investigated whether mosquito bites have any influence on the oncogenesis of EBV-infected NK cells. We examined six HMB patients with EBV-infected NK cell lymphocytosis. We first demonstrated that CD4+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 20 publications
0
29
0
4
Order By: Relevance
“…Representative data are shown. NK cell counts were significantly more in the culture with SGE than the culture without SGE [41]. …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Representative data are shown. NK cell counts were significantly more in the culture with SGE than the culture without SGE [41]. …”
Section: Discussionmentioning
confidence: 85%
“…A remarkable increase in the expression of LMP1 mRNA was observed in the patients' PBMC stimulated with mosquito SGE compared to the PBMC without stimulation[41].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Severe hypersensitivity to mosquito bites is characterized by intense local skin reactions and systemic symptoms such as high fever, lymphadenopathy, and hepatosplenomegaly. These patients often have natural killer cell lymphocytosis associated with chronic Epstein-Barr virus infection (Asada et al 2005, Asada 2007.…”
Section: Immune Response To Mosquito Salivary Productsmentioning
confidence: 99%
“…Several cases have been described in which sensitization to mosquito bites is accompanied with natural killer (NK) cell lymphoproliferative disorders, the presence of T cells infected with Epstein-Barr virus or lymphocytosis associated with HIV infection [29,30,31,32]. The study by Asada et al [33] demonstrated that mosquito saliva induces lymphoproliferation, which, in turn, increases the expression of an oncogene in NK cells, which apparently plays an important role in the etiology of mosquito allergy. It has been shown that the inflammatory and/or allergic response induced by mosquito bites, especially Anopheles spp., favors infection with Plasmodium spp., thereby facilitating the occurrence of malaria [34,35].…”
Section: Introductionmentioning
confidence: 99%